An economic analysis of public government expenditure and its role in attracting foreign direct investment in Iraq during the Period 2004–2022 - Sami Kamil Abd (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial, 2026)
This research aims to analyze the economic contribution of public spending to attracting foreign direct investment in Iraq during the period 2003–2023. Government spending is considered a key tool of fiscal policy that can improve the investment climate and boost economic activity. Public spending, particularly investment spending on developing the country's infrastructure, contributes to creating a suitable economic environment for attracting foreign capital. The research employed a descriptive-analytical approach to analyze the relationship between public expenditures and foreign direct investment (FDI) inflows in Iraq during the study period, using annual data from official bodies and international organizations. The study concluded that a relationship exists between public expenditures and FDI, as increased government spending contributes to improving infrastructure and economic services in Iraq. This enhances foreign investor confidence and encourages investment flows into the Iraqi economy. The findings also demonstrated that weak political and economic stability, coupled with heavy reliance on the oil sector, are among the most significant challenges hindering Iraq's ability to attract further foreign investment. The study recommended redirecting public spending towards productive sectors and infrastructure, improving the investment climate, strengthening economic and legislative stability, and enhancing administrative procedures and modernizing investment laws to increase foreign direct investment inflows and support economic development in Iraq.